A novel nucleic acid aptamer tag: a rapid fluorescence strategy using a self-constructing G-quadruplex from AGG trinucleotide repeats. Issue 81 (26th September 2018) - Fu, Boshi; Park, Yoojin; Kim, Ki Tae; Chen, Kun; Zou, Guangrong; Wei, Qi; Peng, Shuang; Chen, Yuqi; Kim, Byeang Hyean; Zhou, Xiang
Abstract : Herein, we have developed a novel fluorescence labeling strategy for nucleic acid aptamers based on self-assembling between AGG tri-nucleotide repeats and a pyrene-modified oligonucleotide. Abstract : Herein, we have developed a novel fluorescence labeling strategy for nucleic acid aptamers based on self-assembling between AGG tri-nucleotide repeats and a pyrene-modified oligonucleotide. This strategy could be an effective tool for developing targeting–imaging systems and biosensor systems to detect target molecules.